Single parenting: a perspective from young adult children - Burrow, Tess Kira (Kansas State University, 2015)
Single parenting has become a part of American society, yet it seems that through stereotyping and shaming these parents are looked down upon. Often times, single parents do not have the same resources as two parent homes, but single parents can still be effective and raise well-rounded children. This is a qualitative study that sought to provide a different perspective of single never-married parents by interviewing their young adult children. This study focused on the experiences of the young adult children and used Family Stress Theory to help understand and capture specific moments in their lives.
Keywords: Single parent; Single parent families; Children of single parents; Parents; Stress; Resources; Young adults; Early Childhood Education (0518); Ecology (0329); Home Economics (0386); Home Economics Education (0278)